MUHAMMADIYAH DAN POLITIK DAKWAH - Shobron, Sudarno (Tajdida, 2015)
Muhammadiyah as a missionary movement of amar maâruf nahi munkar has similarities and differences with other Islamic movements which are equally as a missionary movement. The equation is like to build Indonesia in accordance with the teachings of Islam in all aspects of life. The difference lies in the strategy of preaching, there are through structural which came to power and there are cultural that are to create an Islamic society. Muhammadiyah political daâwah depicted in its efforts to make improvements in peoples lives, both in the field of religious understanding, economic, social, cultural, educational and defense and security, with the target individual or institutional, economic, political, state, social and cultural sectors.